Physical Activity and Breast Cancer Risk Among Women in the Southwestern United States - Slattery, Martha L. (2007)
Physical activity may influence breast cancer risk through multiple mechanisms and at different periods in life. In this study we evaluate breast cancer risk associated with total and vigorous physical activity at ages 15, 30, and 50 years and the referent year prior to diagnosis/selection. Participants were non-Hispanic white (NHW) (1527 cases and 1601 control subjects) and Hispanic/American Indian (HAI) (798 cases and 924 controls) women. Both total and vigorous activity reduced risk of breast cancer in a dose-response manner. Among premenopausal women, only high total metabolic equivalent of the task (MET) hours of activity during the referent year was associated with reduced breast cancer risk in NHW women (odds ratio [OR] 0.62; 95% confidence interval [CI] 0.43, 0.91). Among postmenopausal women, physical activity had the greatest influence among women not recently exposed to hormones. Among these women, high total lifetime activity reduced risk of breast cancer for both NHW (OR 0.60; 95% CI 0.36, 1.02; p trend 0.01) and HAI women (OR 0.52; 95% CI 0.23, 1.16; p trend 0.07). Additionally, high total MET hours of activity at age 30 years (OR 0.56; 95% CI 0.37, 0.85) and at age 15 years (OR 0.57; 95% CI 0.38, 0.88) reduced breast cancer risk among postmenopausal NHW women not recently exposed to hormones. Among HAI women, more recent activity performed during the referent year and at age 50 appeared to have the greatest influence on breast cancer risk. Among postmenopausal NHW women. there was a significant interaction between physical activity and hormone replacement therapy (p value, 0.01), while among postmenopausal HAI women, physical activity interacted with body mass index (p value, 0.04). These data suggest that physical activity is important in reducing risk of breast cancer in both NHW and HAI women.